1978
DOI: 10.1128/jb.136.1.318-323.1978
|View full text |Cite
|
Sign up to set email alerts
|

Altered nuclear pore diameters in G1-arrested cells of the yeast Saccharomyces cerevisiae

Abstract: Nuclear pores in cells of the yeast Saccharomyces cerevisiae were examined by using the freeze-fracture technique. Nuclear pore diameters in actively growing cells appear to be exclusively of the normal diameter (75 to 115 nm), whereas some pore diameters in abnormally small Gl-arrested cells produced by nitrogen starvation are unusually wide (120 to 160 nm). There may be a correlation between nuclear pore size and nuclear envelope size, the larger pores tending to occur in the smaller envelopes. The finding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Complementary data gained from different fractions showed that the yeast NPC is also significantly smaller than vertebrate NPCs. This has been reported by others (Moor and Miihlethaler, 1963;Severs et al, 1976;Willison and Johnston, 1978). However the overall morphology and the diameters of the central pore and plug within appear to be conserved.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Complementary data gained from different fractions showed that the yeast NPC is also significantly smaller than vertebrate NPCs. This has been reported by others (Moor and Miihlethaler, 1963;Severs et al, 1976;Willison and Johnston, 1978). However the overall morphology and the diameters of the central pore and plug within appear to be conserved.…”
Section: Discussionsupporting
confidence: 80%
“…Thus it is not clear whether the isolated NPCs retained such rings, nor if they are present in yeast NPCs at all. Surprisingly, the measurements obtained from the NPCs within the context of the yeast nuclei were very similar to those obtained from the isolated NPCs (Table IO, though they are in full agreement with the dimensions of NPCs as seen in preparations of yeast cells (Moor and Miihlethaler, 1963;Severs et al, 1976;Willison and Johnston, 1978;Byers, 1981).…”
Section: Electron Microscopy Of the Npc Fractionssupporting
confidence: 74%
“…Pore complexes in actively growing yeast cells appear to have a normal diameter (,x,100 nm), and are present at a frequency ("~11 pores/~m 2) identical to that in many other cell types (14,18). Interestingly, slow growth or growth arrest results in fewer pores per nucleus or an increase in pore diameter (14,28). Pore synthesis during interphase of the yeast cell cycle may be comparable to that in higher eucaryotes (14,19,22).…”
mentioning
confidence: 94%
“…The model shows that despite the initial size differences the generation times of the mother and daughter cells are equal. small yeast cells was reported recently by Willison and Johnston (30). They showed that the nuclear pores of small Gl-arrested cells were larger in diameter than those of large Gl-arrested cells.…”
Section: Resultsmentioning
confidence: 62%